CONCEPTUAL APPROACHES TO STUDENT-CENTERED EDUCATION IN HIGHER EDUCATION - Muxammadiyeva Nilufar Sheraliyevna (The Conference Hub, 2025)
This article analyzes modern paradigms and conceptual approaches to training specialists in higher education institutions. It examines the student-centered learning model, interaction between teachers and students, as well as cognitive and activity-based paradigms. The author emphasizes the need for the humanization of the educational process and outlines the fundamental principles of the pedagogical approach. Additionally, the importance of integrating modern technologies and innovative methods in higher education is discussed.
Keywords: Conceptual approach, Paradigma, Conceptuality, Constructive, Cognitive, Person-centered education, Social responsibility, Creativity